VD_FINDINFO Pron / 2013 / 39 vom 31. Januar 2013 - VD Tribunal cantonal (2013)
DÉCISION D'IRRECEVABILITÉ, EXPERTISE, DOMMAGE IRRÉPARABLE | 239 al. 1 CPC, 239 CPC, 291 CPC, 319 CPC (CH), 319 let. b ch. 2 CPC (CH)